Pharmacognostic Study and Antioxidant Activity of Mundar (Garcinia forbesii King.) leaves from Banua Botanical Gardens of South Kalimantan - Sutomo Sutomo; Dina Noor Kamali; Arnida Arnida; Normaidah Normaidah; Agung Sriyono (Borneo Journal of Pharmacy, 2020)
Mundar (Garcinia forbesii King.) is a plant from South Kalimantan. This plant has chemical contents that have potential as medicine. The purpose of this study is to provide a pharmacognostic picture of a specific, nonspecific and determine the antioxidant activity of G. forbesii leaves. Specific parameters include organoleptic, microscopic testing, thin-layer chromatography profiles, and phytochemical screening. Nonspecific parameters include total ash content, acid insoluble ash content, drying loss, water-soluble extract content, and ethanol-soluble extract content. Antioxidant activity was determined by the DPPH method based on IC50 values. Specific parameter test results are green powder, characteristic odor, and sour taste. Microscopic tests showed stomata, upper epidermis, lower epidermis, cell walls, xylem, phloem, palisade tissue, spongy tissue, and cuticles. Garcinia forbesii leaves contain alkaloids, flavonoids, phenols, tannins, and steroids. The TLC profile showed good separation of polar eluents, and yellow spots appeared after spraying DPPH reagents. The non-specific parameter test is the total ash content of 6.52±0.1%; acid insoluble ash content 1.06±0.08%; drying shrinkage 6.43±0.38%; water-soluble extracts 34.3±0.3%; and ethanol-soluble extracts 23.47±0.35%. Ethanol extract of G. forbesii leaves has antioxidant activity with IC50 of 65.7 ppm. Pharmacognostic study fulfills the requirements, and G. forbesii leaves extract has strong antioxidant activity.